Association between metabolic score for insulin resistance and cardiovascular disease mortality in patients with rheumatoid arthritis: evidence from the NHANES 1999-2018 - Zhou, Yan; Gao, Jie (Frontiers in Endocrinology, 2024)
Aim: To explore the association between Metabolic Score for Insulin Resistance (METS-IR) and the risk of cardiovascular disease (CVD) death in patients with rheumatoid arthritis (RA). Methods: This retrospective cohort study extracted data on 1,218 RA patients from the National Health and Nutrition Examination Survey. The weighted univariate and multivariate Cox regression model was established to explore the association between METS-IR and CVD mortality. Subgroup analysis was performed in terms of age, gender, body mass index, diabetes, and CVD. Hazard ratios (HRs) and 95% confidence levels (CIs) were presented. Results: Increased METS-IR was associated with a significantly higher risk of CVD mortality (HR=4.59, 95%CI: 1.98-10.67), and METS-IR>2.48 was associated with higher odds of CVD mortality compared with METS-IR≤2.25 (HR=3.57, 95%CI: 2.04-6.24). METS-IR was positively associated with the risk of CVD mortality (HR=3.83, 95%CI: 1.62-9.08), and METS-IR>2.48 was associated with a significantly higher risk of CVD mortality in contrast to METS-IR≤2.25 (HR=3.38, 95%CI: 1.87-6.09). Conclusion: Increased METS-IR was associated with a significantly higher risk of CVD mortality in RA patients. Clinicians could consider incorporating the METS-IR score into routine assessment of the prognosis of RA patients.